Legal Status of Ministerial Decree No. 21/2024 and Notaries–Land Deed Officials Roles in Land Rights Transfer for Catholic Church Entities - Dismas Valens Salettia; Daria Daria; Theodorus Pangalila (Nomos : Jurnal Penelitian Ilmu Hukum, 2025)
Existing studies on land-rights transfers involving religious legal entities in Indonesia have predominantly adopted an administrative and certainty-oriented perspective, with limited attention to the theoretical implications of expanding state administrative authority over legal professions. This study examines the legal status of Ministerial Decree of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 21/PNJ/KEM-ATR/BPN/VI/2024 within Indonesia’s land law framework and analyzes its impact on the reconfiguration of the roles of Notaries and Land Deed Officials (PPAT) in land-rights transfers conducted by Roman Catholic Church legal entities. Employing a normative juridical approach through statutory, conceptual, and document analysis, this research explores how the decree not only clarifies eligible holders of the Right of Ownership but also broadens due-diligence standards and professional responsibilities by integrating mandatory permit requirements into pre-deed verification and land registration stages. The findings demonstrate that the decree functions as an instrument of delegated administrative authority that enhances formal legality while simultaneously transforming Notaries and PPAT from administrative executors into verificatory actors within state-regulated religious land policy.